The Macroeconomic Relevance of Credit Flows : An Exploration of U.S. Data - Herman, Alexander (IMF Working Papers; Working Paper ;, 2015)
This paper exploits the Financial Accounts of the United States to derive long time series of bank and nonbank credit to different sectors, and to examine the cyclical behavior of these series in relation to (i) the long-term business cycle, (ii) recessions and recoveries, and (iii) systemic financial crises. We find that bank and nonbank credit exhibit different dynamics throughout the business cycle. This diverging cyclical behavior of output and bank and nonbank credit argues for placing greater emphasis on sector-specific macroprudential measures to contain risks to the financial system, rather than using interest rates to address any vulnerabilities. Finally, we examine the role of bank and nonbank credit in the creation of financial interconnections and illustrate a method to conduct macro-financial stability assessments.